Strengths and Weaknesses of Using Electronic Money as a Substitute for Cash - Ella Anastasya Sinambela; Didit Darmawan (Journal of Social Science Studies (JOS3), 2022)
Economic activities that utilize the sophistication of information technology that helps make it easier for people to make buying and selling transactions. The use of electronic money as an alternative to non-cash payment instruments shows considerable potential to suppress the growth rate of cash use. This study aims to determine the advantages and disadvantages of using electronic money as a substitute for cash. The results of this study are that people like the advantages of electronic money, such as how to transact with electronic money which is known to be relatively easy, just by bringing the electronic money card closer to the reader or just by scanning the chip, people can make payment transactions. Meanwhile, the drawback is that it cannot be used in all places for financial transactions such as cash, because it can only be used at merchants who have collaborated with electronic money issuers and are usually widely available in big cities. Not guaranteed by deposit insurance institutions, and the safety factor.